Partisanship and the gender gap: support for gender quotas in Australia. Issue 3 (3rd July 2018) - Beauregard, Katrine
ABSTRACT: The percentage of women elected in the Australian Parliament is comparatively low. This poor track record has generated debate within political parties about the necessity of gender quotas (or targets) to increase women's representation. Using the 2016 Australian Election Study, this paper proposes to test support for different measures aiming to increasing women's representation in Australian politics. More specifically, I investigate the role of partisanship in explaining gender differences in support for gender quotas. I find that differences in support for quotas are greater among women, and among men, than between women and men. The paper also demonstrates that the role of political values in explaining differences in support for gender quotas is non-uniform. Indeed, attitudes towards government intervention, minority rights, and gender equality are more crucial in explaining differences in support for legislative quotas among men than among women.